Innate and learned predator recognition in four strains of captive-bred atlantic salmon, Salmo salar - Lau, Malcolm J (Scholarship@Western, 2016)
Innate and learned anti-predator responses can be important determinants of survival in natural environments. However, few studies have examined population differences in these anti-predator responses. My study measured innate and learned anti-predator responses in four strains of Atlantic salmon, Salmo salar, which had varying captive breeding histories. All four strains of salmon tested had an innate anti-predator response to alarm cue and no response to a visual predator cue. Following training in which the alarm cue and predator cue were paired, I found that one of the four strains (Sebago), developed a learned anti-predator responses as indicated by reduced activity in response to the predator cue. The duration of captive breeding could not explain why only the Sebago strain showed an ability to learn, suggesting that other factors affect the evolution of learned anti-predator responses. Understanding population variability in learning ability may be important when selecting populations for reintroduction efforts.